Reporting Clinical Results of EPID-Based Patient-Specific Quality Assurance for Brain Stereotactic Radiosurgery/Radiation Therapy: Demonstrating the Feasibility of Same-Day Stereotactic Radiosurgery via HyperArc Delivery - Damodar Pokhrel, PhD; Josh Misa, MS; Shane McCarthy, BS; William St. Clair, MD, PhD (Advances in Radiation Oncology)
Purpose: Patient-specific quality assurance (PSQA) of complex volumetric modulated arc therapy plans via Electronic portal imaging device (EPID)-based portal dosimetry (PD) is widely adopted by the radiation therapy community. We report our EPID-based PSQA results for brain HyperArc stereotactic radiosurgery/radiation therapy (SRS/SRT) patients, justifying its efficiency for the potential of same-day LINAC-based radiosurgery. Methods and Materials: A total of 130 brain SRS/SRT patients were treated via highly conformal HyperArc delivery for 1, 3, and 5 fractions of 18–24 Gy, 24–27 Gy, and 30–35 Gy to each lesion in either single-isocenter/single-lesion (SISL, 60 plans) or single-isocenter/multilesion (SIML, 70 plans) setting following the Alliance brain SRS/SRT clinical trial criteria. Acuros-based dose engine for 6MV-FFF beam (1400 MU/min) was used. For each HyperArc SRS/SRT plan, EPID-based PD PSQA was performed. Independent dose verification of these brain SRS/SRT plans was done via an in-house Monte Carlo (MC) program. The PSQA results, total quality assurance (QA) time, MC agreement, and MLC modulation (MF) were analyzed. Results: The average gamma passing rates were 99.4% (SISL) and 96.9% (SIML) plans with a 2%/2mm clinical gamma criteria. Compared to SISL plans, SIML plans had a higher average MF by a factor of 1.2, maximum of 1.4. We observed a slight correlation between MF and the number of treated lesions. Although SIML plans had relatively lower PSQA pass rates, all plans met the clinical QA criteria for HyperArc delivery. EPID-based PSQA was completed in ∼15 minutes. Moreover, an independent second physics check via in-house MC dose verification was within ±5% compared to AcurosXB calculation and completed within 15 minutes for both treatment schemes including ARIA documentation. Conclusions: These promising PSQA results for complex clinical HyperArc brain SRS/SRT plans delivered in a timely manner via EPID-based PD and independent MC second check demonstrate EPID-based PD is a fast, safe, and efficient QA method for HyperArc treatments. With proper automation of contouring tool and SRS planning via RapidPlan model, this EPID-based PSQA method can be safely implemented for the same-day HyperArc delivery of high-quality brain SRS/SRT treatments in the near future.